Llamas and alpacas in Europe: Endoparasites of the digestive tract and their pharmacotherapeutic control. Issue 3 (June 2015) - Franz, Sonja; Wittek, Thomas; Joachim, Anja; Hinney, Barbara; Dadak, Agnes M.
Highlights: Endoparasitosis is a major health concern in llamas and alpacas. There is a lack of studies on safety and efficacy for most anthelmintics. The potential risk of either underdosing or overdosing is high. Abstract: There are distinctive specifications for veterinary medical care of South American camelids (SACs), namely, llamas, alpacas, vicunas and guanacos. Camelids are classified as food-producing animals, but as veterinary medicinal products are often only licensed for domestic food-producing species such as horses, goats, sheep and cattle, treatment of SACs generally requires off-label use of drugs. Endoparasitism is a major health concern in camelids and can result in severe clinical diseases and economic losses. There is still a lack of work on the pharmacokinetics, safety and efficacy for most antiparasitic drugs used in SACs. Even when choosing an appropriate route of administration, several aspects must be considered such as the fact that pour-on formulations are largely ineffective in camelids due to the unique features of llama and alpaca skin and hair that result in extremely low drug bioavailability. This review focuses on the main endoparasites of the digestive tract in llamas and alpacas in Europe and pharmacotherapeutic options based on current knowledge.